Mindfulness and its correlates in oncological patients - Wesołowska, Karolina; Izdebski, Paweł; Kawiecka-Dziembowska, Bożena (Psychoonkologia, 2015)
The aim of this study was to examine whether mindfulness, defined as receptive awareness and attention focused on current experiences, is associated with anxiety, depression, aggression, and specific ways of coping with cancer. The sample consisted of 100 adults (51 female and 49 male) with different types of cancer. Most of the participants were middle-aged and older (M = 54.93). All patients completed a battery of tests including: the MAAS, the HADS-M, and a modified version of the Ways of Coping – Cancer Version. Our results showed that there is a negative association between mindfulness and the analyzed variables. This suggests that cancer patients might benefit from developing mindfulness.